Successful treatment of immune reconstitution inflammatory syndrome-related hemophagocytic syndrome in an HIV patient with primary effusion lymphoma - Markela Pagonitsa Zorzou; Maria Chini; Athina Lioni; Georgios Tsekes; Thomas Nitsotolis; Ioannis Tierris; Nicolaos Panagiotou; Dimitra Rontogianni; Nicolaos Harhalakis; Marios Lazanas (Hematology Reports, 2016)
Although the connection of [secondary hemophagocytic syndrome (sHS)] with HIV has been well documented, optimal treatment regimen is not well established. This is due not only to the rarity of the syndrome, but also to the heterogeneity of the involved population. Most cases are related to opportunistic infections or malignancies in advanced stage, but many cases are also related to seroconversion, in the primary infection setting. Moreover, in the [antiretroviral treatment (ART)] era, rare cases of ART-related sHS have been reported. In these, often fatal cases, an [immune reconstitution inflammatory syndrome (IRIS)] process is involved, posing a serious challenge to the treating physician. We hereby report a case of successful treatment of an HIV patient with primary effusion lymphoma who experienced sHS shortly after ART onset. Our patient, treated with high dose dexamethasone and gamma globulin, achieved complete remission. This case might hint possible therapeutic insights in the treatment of IRIS-related sHS.